2005
DOI: 10.1364/ol.30.001500
|View full text |Cite
|
Sign up to set email alerts
|

Discretely tunable, all-solid-state laser in the green, yellow, and red

Abstract: We report an all-solid-state intracavity Raman laser with intracavity nonlinear sum-frequency generation providing visible output wavelengths selected from second harmonics and sum frequencies of the fundamental and Stokes fields. The laser comprises a diode end-pumped Nd:YAG laser, an acousto-optic Q switch, a KGd(WO4)2 Raman crystal, and a lithium borate nonlinear converter in a resonator designed to accommodate dynamic thermal lensing. For 20 W of pump power, output powers up to 1.8 W are demonstrated at wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(26 citation statements)
references
References 5 publications
(3 reference statements)
0
26
0
Order By: Relevance
“…Lower output powers were obtained at longer wavelengths, because both the resonator mirrors were 20-30% transmitting at the second-Stokes wavelength (1273 nm). We also found that the powers generated at the sum frequencies were lower than that at the second harmonics [57].…”
Section: Review Of Selected Resultsmentioning
confidence: 52%
See 4 more Smart Citations
“…Lower output powers were obtained at longer wavelengths, because both the resonator mirrors were 20-30% transmitting at the second-Stokes wavelength (1273 nm). We also found that the powers generated at the sum frequencies were lower than that at the second harmonics [57].…”
Section: Review Of Selected Resultsmentioning
confidence: 52%
“…To our knowledge, wavelength-selectable lasers based on intracavity SHG/SFG of intracavity Raman lasers have been reported only by Ammann [14,62] and ourselves [57,69].…”
Section: Review Of Selected Resultsmentioning
confidence: 99%
See 3 more Smart Citations